1981
DOI: 10.1177/002194368101800303
|View full text |Cite
|
Sign up to set email alerts
|

Developing Leadership Skills in Nonverbal Communication: A Situational Perspective

Abstract: This paper addresses the importance of developing leadership skills in the encoding and decoding of nonverbal messages. It takes the position that impressions formed in superior-subordinate relationships are often determined by the nonverbal communication that occurs in face-to-face meetings. Based on social exchange principles, a situational view of considerate leadership behavior is developed where a superior attempts to make interaction less costly and aversive to subordinates by adapting to them nonverball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…Models of emotion in negotiation also note that negative affect resulting from goal conflict or unmet expectations may elicit dominant action tendencies in negotiators (Barry and Oliver 1996;Butt, Choi, and Jaeger 2005;Kumar 1999). Dominance is generally associated with being forceful, assertive, and expressive (Burgoon and Dunbar 2000;Manusov 2005), the nonverbal display of which includes the use of space, relaxed posture, and emotion expressiveness, especially negative emotions (Mehrabian 1974;Remland 2009). …”
Section: Nonverbal Display Of Dominance In Negotiationmentioning
confidence: 99%
See 3 more Smart Citations
“…Models of emotion in negotiation also note that negative affect resulting from goal conflict or unmet expectations may elicit dominant action tendencies in negotiators (Barry and Oliver 1996;Butt, Choi, and Jaeger 2005;Kumar 1999). Dominance is generally associated with being forceful, assertive, and expressive (Burgoon and Dunbar 2000;Manusov 2005), the nonverbal display of which includes the use of space, relaxed posture, and emotion expressiveness, especially negative emotions (Mehrabian 1974;Remland 2009). …”
Section: Nonverbal Display Of Dominance In Negotiationmentioning
confidence: 99%
“…According to Remland (1981), powerful and dominant individuals tend to have more access to space and larger territories. Previous studies illustrate that when people expand themselves by occupying space, they are perceived as dominant, and postural expansion is more likely to occur amongst high status individuals (Argyle 1988;Aries, Gold, and Weigel 1983;Mehrabian 1972;Tiedens and Fragale 2003).…”
Section: Nonverbal Display Of Dominance In Negotiationmentioning
confidence: 99%
See 2 more Smart Citations
“…But Remeland (1981) has found that high-status persons act in ways that control, or attempt to control, the time of others. The implication is that management may attempt to &dquo;force&dquo; the communication on employees at a time desirable only to management.…”
Section: Timementioning
confidence: 99%